2017
DOI: 10.1038/s41598-017-06871-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Very Early Mobilization in Patients with Acute Stroke: A Systematic Review and Meta-analysis

Abstract: Whether very early mobilization (VEM) improves outcomes in stroke patients and reduces immobilization-related complications (IRCs) is currently unknown. The objective of this systematic review and meta-analysis was to evaluate the efficacy and safety of VEM in acute stroke patients following admission. Medline, Embase, and Cochrane Central Register of Controlled Trials databases were searched for randomized controlled trials (RCTs) that examined the efficacy or safety of VEM in patients with acute stroke. VEM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 36 publications
2
17
0
5
Order By: Relevance
“…EM is also reported to improve self-care ability or promote early discharge in post-stroke patients [10]. As a result, recent systematic reviews have showed that EM is inconsistently associated with recovery from stroke [11,12]. To clarify these inconsistent results, a subgroup analysis for determining the characteristics associated with ND or worse outcome was conducted [8].…”
Section: Introductionmentioning
confidence: 99%
“…EM is also reported to improve self-care ability or promote early discharge in post-stroke patients [10]. As a result, recent systematic reviews have showed that EM is inconsistently associated with recovery from stroke [11,12]. To clarify these inconsistent results, a subgroup analysis for determining the characteristics associated with ND or worse outcome was conducted [8].…”
Section: Introductionmentioning
confidence: 99%
“…RCT, sebanyak 5 studi mengikutsertakan pasien dengan berbagai macam tipe stroke, 3 studi dengan stroke iskemik, dan 1 studi dengan stroke perdarahan (Xu et al, 2017 (Olkowski & Shah, 2017). (Olkowski & Shah, 2017).…”
Section: Mobilisasi Dini Pada Stroke Iskemikunclassified
“…VEM cenderung aman dan tidak berhubungan dengan risiko yang lebih tinggi dalam kematian dan tidak meningkatkan risiko perburukan neurologis, serta kejadian jatuh pada stroke. Sebagai simpulan VEM tidak berhubungan dengan efek yang bermanfaat ketika dilakukan pada pasien 24 -48 jam pasca onset (Xu et al, 2017)…”
unclassified
“…VEM tidak meningkatkan risiko kematian dan kerusakan neurologis, serta tidak meningkatkan resiko jatuh dengan cedera selama mobilisasi. 10 Alain P. Yelnik dkk pada tahun 2016 melakukan penelitian multicenter uji coba terkontrol acak Active Mobility Very Early After Stroke yang dilakukan pada 103 pasien stroke dengan melakukan mobilisasi dini pada 25 -72 jam pertama disertai latihan fisik intensif tidak terbukti efisien dalam meningkatkan kontrol motorik. 7 Penelitian lain membahas mengenai late mobilization, Mohammad Usman Khan dkk pada tahun 2014 melakukan penelitian cross sectional pada 100 orang pasien dari 3 rumah sakit di Karachi -Pakistan.…”
Section: Prosiding Ilmiah Dies Natalis Fakultas Kedokteran Universitaunclassified